A statistical study on the local time dependence of Equatorial Spread F (ESF) irregularities and their relation to low‐latitude Es layers under geomagnetic storms - Sripathi, S. (My University, 2020)
In this paper, we present a study on the local time dependence of equatorial spread F (ESF) irregularities and their relation to low‐latitude Es layers in response to geomagnetic storms using simultaneous observations of two ionosondes one located at Tirunelveli (8.73°N, 77.70°E), an equatorial station and other located at Hyderabad (17.36°N, 78.47°E), an off‐equatorial station during the years 2007–2015 that covers solar cycles 23 and 24. The Aarons criteria for the ESF irregularities for different seasons under geomagnetic storms are evaluated. In the category I, we noticed partial enhancement in prereversal enhancement (PRE) during postsunset resulting in ~30% occurrence of spread F instead of total inhibition during equinox and winter seasons. Also, occurrence of ESF in summer is suppressed by only ~75% due to partial increase in PRE. In category II, we observed presunrise height enhancement mostly during winter, which caused ESF to occur at ~50% followed by equinox and summer. The results presented here suggest that many are actually not following the Aarons criteria possibly due to not considering other background conditions. Accordingly, we examined the plausible role of low‐latitude Es layers on the generation of ESF irregularities under these categories during geomagnetic storms. We noticed the absence/presence of Es layers in both categories during postsunset and postmidnight hours resulting in increase/decrease of PRE due to modifications in the field‐line‐integrated Pederson conductivity. Accordingly, the results suggest that one of the plausible reasons for ESF irregularities not following Aarons criteria is linked to the variability of the low‐latitude Es layers. Plain Language Summary : The electric fields and winds in the equatorial and low‐latitude ionosphere are modified during geomagnetic storms due to coupling of solar wind‐magnetosphere‐ionosphere in the high latitudes. Accordingly, the occurrence of equatorial spread F (ESF) irregularities are significantly affected by the geomagnetic storms depending upon the time of the onset of the geomagnetic storm. We classified our observations into three categories based on Aarons criteria under different seasons to examine the role of geomagnetic storms on the generation/suppression of ESF irregularities based on the onset conditions of magnetic storms over India. The observations suggest that many ESF events could not follow this criterion due to not having included other background conditions. Accordingly, we examined the role of low‐latitude Es layers, which may affect the field‐integrated conductivities of the E and F regions during the onset times of ESF irregularities using larger data. The results suggest that whenever Es layers are present (absent) at low latitude, suppression (generation) of premidnight or postmidnight ESF irregularities at Tirunelveli is on rise. So these results suggest that if the low‐latitude Es layers are taken into account, occurrence of ESF irregularities may be explained better by the above criteria.
Keywords: EQUATORIAL AERONOMY, Geomagnetic storms, ESF irregularities, Equatorial spread F, Low latitude Es layers